Mechanisms of plant competition for nutrients, water and light. (7th March 2013) - Craine, Joseph M.; Dybzinski, Ray
Summary: Competition for resources has long been considered a prevalent force in structuring plant communities and natural selection, yet our understanding of the mechanisms that underlie resource competition is still developing. The complexity of resource competition is derived not only from the variability of resource limitation in space and time and among species, but also from the complexity of the resources themselves. Nutrients, water and light each differ in their properties, which generates unique ways that plants compete for these resources. Here, we discuss the roles of supply pre‐emption and availability reduction in competition for the three resources when supplied evenly in space and time. Plants compete for nutrients by pre‐empting nutrient supplies from coming into contact with neighbours, which requires maximizing root length. Although water is also a soil resource, competition for water is generally considered to occur by availability reduction, favouring plants that can withstand the lowest water potential. Because light is supplied from above plants, individuals that situate their leaves above those of neighbours benefit directly from increased photosynthetic rates and indirectly by reducing the growth of those neighbours via shade. In communities where juveniles recruit in the shade of adults, traits of the most competitive species are biased towards those that confer greater survivorship and growth at the juvenile stage, even if those traits come at the expense of adult performance. Understanding the mechanisms of competition also reveals how competition has influenced the evolution of plant species. For example, nutrient competition has selected for plants to maintain higher root length and light competition plants that are taller, with deeper, flatter canopies than would be optimal in the absence of competition. In all, while more research is needed on competition for heterogeneous resource supplies as well as for water, understanding the mechanisms of competition increases the predictability of interspecific interactions and reveals how competition has altered the evolution of plants. Abstract : Lay Summary Abstract :